Inclusion, Legislation and Practice: Educating Students With Disabilities – the Australian and Latvian Experiences - Prudņikova, Ilga; Bruveris, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In Australia and Latvia the inclusion debate has changed the face of education. This change has been brought about by legislative edicts, challenges to traditions which segregate students and by confronting teacher beliefs. This article explores the experiences of the education system in Australian, specifically the state of New South Wales (NSW), in addressing inclusion. Parallels between the Australian and Latvian experiences are identified. Finally the retreat by the NSW system away from the confusion surrounding the use of the term inclusion to the concept of every student, every school is detailed.